Charles de Gaulle & the French resistance : a case study on the legitimacy and contention of a resistance and its leader - Schroderus-Nevalainen, Andrina (2014)
Charles de Gaulle, one of the most notable leaders of the French history, rose to power outside democratic processes. When he departed for London in June 1940 to continue the opposition against Germany, de Gaulle was not an elected official nor did he hold a significant governmental post. He was also lacking public support, but nevertheless managed to become the symbol of French resistance and emerge as the leader of post-war France. Years later, he again became the head of his country outside democratic processes, yet history does not question his legitimacy as a leader. This master’s thesis looks into the foundation of de Gaulle’s legitimacy, and attempts to explain why and how he became a legitimate leader.